PENGARUH RETRIBUSI PASAR DAN RETRIBUSI PERSAMPAHAN/ KEBERSIHAN TERHADAP PENDAPATAN ASLI DAERAH KOTA SUKABUMI (Studi Kasus Pada Dinas Pendapatan Pengelola Keuangan Dan Aset Daerah) - Eri Hermawan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
Local Revenues (PAD) is sources of local financing, because the ability of economic performace measured by the extent contributions made by Local Revenues (PAD) to APBD. Local Revenues is sources to local tax result local retribution,result wealth management local separated and others Local Revenues legitimate. Local Retribution divided into 3 type is general service retribution,business services retribution, and certain licensing retribution,in this case author examined in field general service retribution one of them is market retribution and retribution waste. This study analyzed the influence of Market Retribution and Retribution Waste to Local Revenues (PAD) in Sukabumi City period 2011 up to 2015. Variable use this study is Market Retribution, Retribution Waste as variable dependen and Local Revenues (PAD) use variable independen. Respondents in this study is part of the financia statements to revenue department manager, finances and assets local period 2011 up to 2015 Sukabumi City which can be included in data processing. Data analysis using the program SPSS version 22. Statistical methods used to tested the hypothesis is multiple linear regression analysis. After analyzed using t test is find that the partial Market Retribution positive effect of 2,519>2.00247 to Local Revenues (PAD). And to Retribution Waste in partial positive effect of 3,447>2.00247 to Local Revenues (PAD). While Market Retribution and Retribution Waste after in analyzed use f test in simultaneously positive effect of 11% to Local Revenues (PAD) and the rest is influenced by others factors not examined by the author.